2011
DOI: 10.1007/s10140-011-0964-5
|View full text |Cite
|
Sign up to set email alerts
|

Radiological prognostic factors in patients with pandemic H1N1 (pH1N1) infection requiring hospital admission

Abstract: The aim of this study was to determine the radiologic findings associated with admission to the intensive care unit (ICU) and the development of acute respiratory distress syndrome (ARDS) in patients with pH1N1 infection. One hundred and four patients (15-96 years) with laboratory-confirmed pH1N1 infection seen at the Emergency Department from July to December 2009 who underwent chest radiographs were studied. Radiographs were evaluated for consolidation, ground-glass opacities, interstitial patterns, distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 21 publications
3
7
1
Order By: Relevance
“…Two small studies of patients admitted to the ITU demonstrated that bilateral and multi-focal changes on the presenting chest X-ray, was more likely to require ITU admission and progression to an ARDS type appearance [7,8]. In our study, the length of inpatient hospital stay was longer in the H1N1 cohort, compared with non-H1N1, although this did not quite reach statistical significance.…”
Section: Length Of Stay Median Days (Iqr) P-valuecontrasting
confidence: 75%
See 2 more Smart Citations
“…Two small studies of patients admitted to the ITU demonstrated that bilateral and multi-focal changes on the presenting chest X-ray, was more likely to require ITU admission and progression to an ARDS type appearance [7,8]. In our study, the length of inpatient hospital stay was longer in the H1N1 cohort, compared with non-H1N1, although this did not quite reach statistical significance.…”
Section: Length Of Stay Median Days (Iqr) P-valuecontrasting
confidence: 75%
“…Several studies have reported on the chest X-ray phenotype, some suggesting prognostication of H1N1 disease by chest Xray appearance and further studies of serial imaging, which have demonstrated lung infiltration and progression to acute respiratory distress syndrome (ARDS) [6][7][8]. However, at the point of presentation, it would be necessary to identify H1N1 rapidly and differentiate it from the less aggressive community acquired pneumonias.…”
Section: H1n1 a New Influenzamentioning
confidence: 96%
See 1 more Smart Citation
“…According to the literature, some patients may have a normal chest radiograph at first presentation, but may develop alveolar opacities and bilateral interstitial infiltrates on chest radiographs in the following days (12,21). It was reported that radiological findings were more often bilateral in patients who underwent mechanical ventilation due to severe respiratory failure (4,21,22). Even where no radiological evidence of disease is initially detected, radiological findings may subsequently emerge and serious respiratory failure may develop over a short period.…”
Section: H1n1mentioning
confidence: 99%
“…A rapid progression of the radiological abnormalities and development of acute respiratory distress syndrome (ARDS) can be identified in patients requiring PICU admission (15,26). In one of our patients, while the X-ray was normal at admission, bilateral patchy opacities at basal regions appeared in the thorax CT scan after 4 h of admission, and ARDS developed after 18 h of admission.…”
mentioning
confidence: 69%